Quality by design based optimization and physicochemical characterization of flucytosine nanoemulsion - Rajat Srivastava; Ajay Kumar Singh Rawat (Creative Pharma Assent, 2026)
Background: The rise of pathogenic fungi capable of infecting people is a major public health problem. Flucytosine is an effective antifungal agent, but its clinical use is constrained by rapid clearance and dose-related adverse effects. Nanoemulsion-based systems offer a promising strategy for drug delivery and therapeutic performance. The objective of this work was to develop and optimize a flucytosine-loaded nanoemulsion using a Quality by Design (QbD) approach based on the Box-Behnken design, and to evaluate its physicochemical characteristics. Methodology: A Box-Behnken design (BBD) was used to optimize formulation factors, including lipid concentration, Smix (surfactant-to-cosurfactant) ratio, and homogenization time, using high-speed homogenization. The impacts on particle size, polydispersity index, and entrapment efficiency (EE) were investigated. UV-visible spectroscopy, Fourier-transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD) were used to assess the compatibility and stability of the improved formulation (F11) with the chosen excipients. Results and Discussion: The optimized formulation (F11) had a particle size of 318.18 nm and a PDI of 0.136, a zeta potential of -22.2 mV, and high entrapment efficiency (96.36%), indicating good stability and uniformity. Preformulation and compatibility studies confirmed the absence of drug-excipient interactions. Statistical analysis demonstrated that formulation variables significantly influenced critical quality attributes. Conclusion: The study demonstrates that QbD-driven optimization can successfully develop a stable and efficient flucytosine nanoemulsion with enhanced drug-loading capacity and potential to improve antifungal therapy. However, further studies, including in vitro drug release, in vivo evaluation, long-term stability, and clinical validation, are required to confirm its performance in drug delivery applications.